1994
DOI: 10.1016/0167-6296(94)90022-1
|View full text |Cite
|
Sign up to set email alerts
|

Market work, wages, and men's health

Abstract: In this paper, we investigate the complex interrelations among work-time, wages, and health identified in the Grossman model of the demand for health. Hansen's generalized method of moments techniques are employed to estimate a 3-equation simultaneous model designed to capture the time dependent character of these interrelationships. We then estimate simpler models with more restrictive assumptions commonly found in the literature and find substantial differences between these estimates and those from our simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…It is also possible that health affects the income generating capacity of individuals so what is believed to be the impact of income on service uptake is the impact of previous health [31][32][33]. Similarly, previous education has important effects on income and health [18,[28][29][30][31][32][33][34]. Our estimation dealt with these issues by incorporating measurements of average health and well-being from 1991 to 2003 as well as previous educational qualifi cations.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that health affects the income generating capacity of individuals so what is believed to be the impact of income on service uptake is the impact of previous health [31][32][33]. Similarly, previous education has important effects on income and health [18,[28][29][30][31][32][33][34]. Our estimation dealt with these issues by incorporating measurements of average health and well-being from 1991 to 2003 as well as previous educational qualifi cations.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence about the effects of education on health status may be found, among many others, in Berger and Leigh (1989); Grossman and Kaestner (1997); and Kenkel (1991). From more general perspectives, Hartog and Oosterbeck (1998) have explored the multiple relationships among health, wealth, and happiness, and Haveman et al (1994) use a three-equation simultaneous model to provide evidence about the time-dependent nature of the links between work effort, wages and workers' health status.…”
Section: Correlation Between Education and Healthmentioning
confidence: 95%
“…Some of the literature takes a more dynamic approach and uses lagged health as a determinant of the current labour supply. In an early example of this, Haveman et al (1994) estimated a simultaneous equation model for working hours, wages, and health with longitudinal data on 613 white males observed over 8 years from the US Panel Study of Income Dynamics. They found that lagged ill-health (measured by health related work-limitations) reduces wages of men by 54% compared to no limitations.…”
Section: Health and Human Capital: The Empirical Literaturementioning
confidence: 99%